2022
DOI: 10.1017/s0021859622000284
|View full text |Cite
|
Sign up to set email alerts
|

Adding corn meal into mixed elephant grass–butterfly pea legume silages improves nutritive value and dry matter recovery

Abstract: The objective of this study was to describe and explain the effect of adding corn meal (CM) on losses, fermentation characteristics and nutritional value of silages from two elephant grass [Cenchrus purpureus (Schumach.) Morrone] genotypes (Taiwan A-146 2.37 and IRI-381) mixed with butterfly pea (Clitoria ternatea L.) legume. The forage was harvested at 75 days of regrowth from elephant grass plots intercropped with butterfly pea legume and ensiled with or without CM at 5% of dry matter (DM) content. Greater g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…When processing cocoa beans after harvest, local farmers typically remove the cocoa husk, which makes up between 2/3 and 3/4 of the weight of the fruit (the average fruit weighs about 400 g). (Costa et al, 2022) observed a favorable relationship in the chemical compositions of soybean hull, Bermuda grass, and cocoa pod husk. (Omotoso, 2019) stated that ruminants might get a significant amount of their energy needs met by cocoa pod husks.…”
Section: Use Of Cocoa For Agricultural Produc Onmentioning
confidence: 90%
“…When processing cocoa beans after harvest, local farmers typically remove the cocoa husk, which makes up between 2/3 and 3/4 of the weight of the fruit (the average fruit weighs about 400 g). (Costa et al, 2022) observed a favorable relationship in the chemical compositions of soybean hull, Bermuda grass, and cocoa pod husk. (Omotoso, 2019) stated that ruminants might get a significant amount of their energy needs met by cocoa pod husks.…”
Section: Use Of Cocoa For Agricultural Produc Onmentioning
confidence: 90%